Velocity structure of crust and mid-strong earthquake preparation characteristics in the Huoshan region, East China - Hu, Tiantian; Fan, Xiaoping; He, Yicheng; Yang, Longshuai; Yang, Congjie; Jiang, Pengcheng; Liu, Zhiwen; Xia, Ziyan; Xu, Menghui; Wu, Yuhan (Frontiers in Physics, 2024)
The Huoshan region, located on the northern margin of the Dabie Orogenic Belt at the junction of the North China Plate and the Yangtze Plate, is one of the most seismically active and concentrated areas in the Dabie Orogenic Belt and adjacent regions. Utilizing the travel time data from 4,427 seismic events observed by 202 stations, we investigated the deep medium structure of the Huoshan region using the double-difference tomography method. The results reveal the medium structure and characteristics of mid-strong earthquake preparation in the region. The crustal medium in the study area exhibits significant lateral heterogeneity. The Dabie Orogenic Belt shows notably high velocity, whereas the North China Plate and the Yangtze Plate display relatively lower velocities. The Tan-Lu Fault Zone exhibits segmentation characteristics; with the crustal medium velocity south of Lujiang being relatively high, north of Jiashan being relatively low, and between Lujiang and Jiashan being intermediate. The epicenters of mid-strong earthquakes are located on the gradient zones of velocity and Poisson’s ratio. The source regions of these earthquakes show significant anomalies of high Poisson’s ratio and low S-wave velocity, which may indicate the presence of fluids. These anomalies possibly reflect the intrusion of deep materials along the fault zone, which could be the driving force for the preparation of mid-strong earthquakes.